Hand Or Foot Reflexology To Relieve Pain Postpartum: A Systematic Review - Rieh Firdausi; Anggorowati Anggorowati; Sari Sudarmiati (Universitas Respati Yogyakarta, 2020)
Background: Many previous studies have discussed hand and foot reflexology which is useful for reducing postpartum pain. However, previous studies presented different results related to foot massage, time and pain changes, so that in this systematic review aimed at supporting non-pharmacological nursing interventions of the hands and feet reflexology associated with postpartum enhancement by looking at these three types namely : duration of massage, time of massage and changes in pain. Objective: This study aims to analyze the duration, time, and results of hand or foot reflexology in reducing maternal postpartum pain. Methods: A systematic review through maternity nursing articles to analyze the effects of hand or foot reflexology in reducing postpartum pain. Search articles using electronic databases namely Sciene Direct, Pubmed, PMC, Google Schoolar and Scopus. Articles that meet the inclusion criteria will be collected and analyzed systematically. Results: In a systematic review it is explained that hand or foot reflexology can reduce postpartum maternal pain but in the duration and timing of the intervention still need consideration from further researchers. Conclusion: Based on the results of the study, hand or foot reflexology is recommended to reduce pain, specifically postpartum pain